Occurrence and distribution of Salmonella serovars in carcasses and foods in southern Italy: Eleven-year monitoring (2011–2021) - Peruzy, Maria Francesca; Proroga, Yolande Thérèse Rose; Capuano, Federico; Mancusi, Andrea; Montone, Angela Michela Immacolata; Cristiano, Daniela; Balestrieri, Anna; Murru, Nicoletta (Frontiers in Microbiology, 2022)
Salmonella is one of the most common agents of foodborne illness. The genus Salmonella includes two species (Salmonella bongori and S. enterica) and six subspecies (enterica I, salamae II, arizonae IIIa, diarizonae IIIb, houtenae IV, and indica VI), each of which contains multiple serotypes associated with animal and human infections. The aim of the study was to evaluate the presence of Salmonella spp. in carcasses of food-producing animals and foods in southern Italy and the serovar distribution among different sources. From 2011 to 2021, a total of 12,246 foods and 982 samples from animal carcasses were collected and analysed. The overall percentage of positive samples was 5.84% (N = 773) and a significant increase in prevalence was observed by comparing the years 2011-2015 (257, 3.27%) and 2016-2021 (516, 9.61%) (p < 0.05). The highest percentage of positive food samples was observed in “Meat and Meat Products” (N= 327/2,438, 13.41%) followed by “Fish and fishery products” (N= 115/1,915, 6.01%). In carcasses, the highest percentage of positive samples was reported from broilers (N= 42/81, 51.85%) followed by buffalo (N= 50/101, 49.50%) and pork (N= 140/380, 36.84%). After typing, the isolates were assigned to the species S. enterica and to the subspecies: enterica (N = 760, 98.32%), diarizonae (N = 8, 1.03%), salamae (N= 3, 0.39%) and houtenae (N= 2, 0.26%). S. Infantis was the most frequently detected (N= 177, 24.76%), followed by S. Derby (N= 77, 10.77%), monophasic S. Typhimurium (N= 63, 8.81%), S. Typhimurium (N= 54, 7.55%), and S. Rissen (N= 47, 6.57%). By comparing the sampling period 2011–2015 with that of 2016–2021, an increase in the prevalence of S. Infantis and monophasic S. Typhimurium and a decrease of S. Typhimurium were recorded (p < 0.05). Thus, present data suggest that, despite the implementation of national and European control strategies to protect against Salmonella, the prevalence of this pathogen in southern Italy is still increasing and a change of national control programs to protect against Salmonella are necessary.